The study of residents’ attitude towards sociocultural benefits in Penarik, Terengganu / Farah Hanum Mohd Hasnan, Norain Abdullah and Nurul Liana Abdul Halid - Mohd Hasnan, Farah Hanum; Abdullah, Norain; Abdul Halid, Nurul Liana (2015)
This study investigates the host-guest relationship development between locals and tourists in relation with the socio-cultural benefits. It proposes that great communication skill is the major determinant in the successfulness of tourism development towards the community. There are not many studies been conducted in rural areas such as Kampung Penarik, Terengganu. In particular, this research concentrates on the residents’ attitude in tourism and the socio cultural benefits between locals and tourists both domestically and internationally in Kampung Penarik, Terengganu. To assist in the study, a research framework developed by J.E Brougham and R. W. Butler (1981) was modified and used to conceptualize the residents’ attitudes in tourism and socio-cultulral benefits and to inform the data collection procedure. A self-administered questionnaire survey collected 80 respondents, who are the local community. The results of descriptive analysis revealed the importance of English language exposure among the locals towards the sociocultural benefits. The findings of the study also highlighted the collaboration of the government (MOTAC, Tourism Malaysia), private sectors (travel agencies and other tourism-related agencies) and even the local universities together with the local communities will bring a great positive impact in the tourism development of Kampung Penarik, Terengganu.